2005
DOI: 10.1074/jbc.m500694200
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification and Transcriptome Response in Arabidopsis Seedlings Exposed to the Allelochemical Benzoxazolin-2(3H)-one

Abstract: Benzoxazolin-2(3H)-one (BOA) is an allelochemical most commonly associated with monocot species, formed from the O-glucoside of 2,4-dihydroxy-2H-1,4-benzoxazin-3(4H)-one by a two-step degradation process. The capacity of Arabidopsis to detoxify exogenously supplied BOA was analyzed by quantification of the major known metabolites BOA-6-OH, BOA-6-O-glucoside, and glucoside carbamate, revealing that detoxification occurs predominantly through O-glucosylation of the intermediate BOA-6-OH, most likely requiring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
201
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(214 citation statements)
references
References 83 publications
8
201
0
5
Order By: Relevance
“…When tested in the same concentration range as APO and AMPO, the root-exuded precursor substances DIBOA and DIMBOA and the intermediates BOA and MBOA did not inhibit plant HDACs (Supplemental Figure 5). These results were in line with a previous report that the half-maximal effective concentration (EC 50 ) of BOA in a root growth inhibition assay was 540 µM (Baerson et al, 2005), i.e., a concentration 10 times higher than the effective APO and AMPO concentrations for HDAC inhibition. This suggests that the root-secreted precursor substances need to be metabolized or chemically converted to become potent HDAC inhibitors.…”
Section: Inhibition Of Hdacs By Apo and Amposupporting
confidence: 82%
“…When tested in the same concentration range as APO and AMPO, the root-exuded precursor substances DIBOA and DIMBOA and the intermediates BOA and MBOA did not inhibit plant HDACs (Supplemental Figure 5). These results were in line with a previous report that the half-maximal effective concentration (EC 50 ) of BOA in a root growth inhibition assay was 540 µM (Baerson et al, 2005), i.e., a concentration 10 times higher than the effective APO and AMPO concentrations for HDAC inhibition. This suggests that the root-secreted precursor substances need to be metabolized or chemically converted to become potent HDAC inhibitors.…”
Section: Inhibition Of Hdacs By Apo and Amposupporting
confidence: 82%
“…Exposure of Arabidopsis seedlings to the allelochemical benzoxazolin-2(3H)-one (BOA), for example, leads to massive changes in gene expression, including the up-regulation of a large number of detoxification genes (Baerson et al 2005), which showed an overlap of only 11.0% with the safener-inducible genes identified in this study. Likewise, only 11.4% of the detoxification genes induced by phytoprostane A1 (PPA1) were represented in our set of safener-inducible genes, as compared with 28% that were co-induced by BOA and PPA1 (Mueller et al 2008).…”
Section: Discussionmentioning
confidence: 87%
“…In Arabidopsis thaliana, for example, safeners were shown to induce the expression of GSTs and glucosyl transferases (phase II; DeRidder et al 2002;Smith et al 2004;Edwards et al 2005b), glutathione-conjugate transport (phase III; Baerson et al 2005;DeRidder & Goldsbrough 2006) and catabolism (phase IV;Brazier-Hicks et al 2008). Also in hybrid poplar, phase I-III genes were found to be up-regulated after safener treatment (Rishi et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Además existen numerosas investigaciones que revelan que las MDR no sólo están implicados en la desintoxicación, sino también en la regulación celular de almacenaje (Gaedeke et al, 2001;Fekete et al, 2015;Cummins et al, 2015). Se ha encontrado que AT3G59140 (AtMRP14; MRP14) está inducido más de 2,5 veces (fold change) en respuesta a Benzoxazolinona en Arabidopsis (Baerson et al, 2005).…”
Section: Genes Y Factores De Transcripción Que Participan En El Metabunclassified
“…Por otro lado, Baerson et al, (2005) y Fode et al, (2008 enfatizaron el rol central de los factores TGA a la respuesta a xenobióticos. El factor de trascripción TGA del tipo STP1 (Potri.009G164300) (N) del análisis de co-expresión podría participar en la ruta de degradación de xenobióticos.…”
Section: Genes Y Factores De Transcripción Que Participan En El Metabunclassified